2003
DOI: 10.1007/s00442-002-1162-7
|View full text |Cite
|
Sign up to set email alerts
|

Are lichens active under snow in continental Antarctica?

Abstract: Photosynthetic activity, detected as chlorophyll a fluorescence, was measured for lichens under undisturbed snow in continental Antarctica using fibre optics. The fibre optics had been buried by winter snowfall after being put in place the previous year under snow-free conditions. The fibre optics were fixed in place using specially designed holding devices so that the fibre ends were in close proximity to selected lichens. Several temperature and PPFD (photosynthetic photon flux density) sensors were also ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(65 citation statements)
references
References 23 publications
(30 reference statements)
3
61
0
Order By: Relevance
“…being activated by water uptake in the gaseous phase from snow at subzero temperatures. Nevertheless, there is little evidence that activation by water vapour occurs naturally in Antarctica (Hovenden et al, 1994;Pannewitz et al, 2003). Here, we found that the BSC from Site Darwin dominated by the green algal lichen Acarospora gwynnii did not reactivate from water vapour alone.…”
Section: Photosynthetic Performancementioning
confidence: 51%
“…being activated by water uptake in the gaseous phase from snow at subzero temperatures. Nevertheless, there is little evidence that activation by water vapour occurs naturally in Antarctica (Hovenden et al, 1994;Pannewitz et al, 2003). Here, we found that the BSC from Site Darwin dominated by the green algal lichen Acarospora gwynnii did not reactivate from water vapour alone.…”
Section: Photosynthetic Performancementioning
confidence: 51%
“…One example used in ecological field campaigns are the measurements on metabolic activity such as measuring methane production by methanogens (Wagner et al 2005(Wagner et al , 2007 or photosynthetic activity by phototrophs like cyanobacteria, alga and lichens (Lange 1969;Lange et al 1970;Schroeter et al 1994;Schroeter and Scheidegger 1995;Pannewitz et al 2003). Also, reproduction expressed by the growth rate may be recorded, which might take several years of continuously monitoring the selected field sites in order to obtain measurement results over longer time scales.…”
Section: Planetary Field Analogue Environments On Earthmentioning
confidence: 99%
“…Furthermore, it changes the dynamics of the water supply and the temperature regime compared to a situation without snow cover. It is assumed in the model that lichens and bryophytes are not able to photosynthesise if the snow cover above them exceeds a certain critical thickness p snow (Pannewitz et al, 2003). Since it is impractical to simulate the water content of the organisms under snow, dark respiration is also assumed to be negligible in this situation.…”
Section: B45 Snow Layermentioning
confidence: 99%